A review of human carcinogens. Part A: pharmaceuticals (Lyon, 2012)
"This Volume 100A covers Pharmaceuticals, specifically Busulfan, Chlorambucil, Methyl-CCNU, Cyclophosphamide, Etoposide in combination with Cisplatin and Bleomycin, Melphalan, MOPP, Tamoxifen, Thiotepa, Treosulfan, Diethylstilbestrol, Estrogen-only Menopausal Therapy, Combined Estrogen-Progestogen Menopausal Therapy, Combined Estrogen-Progestogen Contraceptives, Azathioprine, Chlornaphazine, Ciclosporin, Plants containing Aristolochic Acid, Methoxsalen plus Ultraviolet A Radiation, and Phenacetin.